2007
DOI: 10.1158/0008-5472.can-07-1791
|View full text |Cite
|
Sign up to set email alerts
|

RNA Interference Inhibition of Matrix Metalloproteinase-1 Prevents Melanoma Metastasis by Reducing Tumor Collagenase Activity and Angiogenesis

Abstract: Melanoma incidence is increasing worldwide, and metastatic melanoma is almost completely resistant to every known therapy. New approaches to treating melanoma are urgently needed, and a greater understanding of the biology of melanoma invasion and metastasis will aid in their creation. A high proportion of invasive melanomas have a constitutively active Raf/mitogen-activated protein kinase/extracellular signal-regulated kinase (MEK/ERK) signaling cascade; however, the downstream effectors of ERK signaling that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
92
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(95 citation statements)
references
References 38 publications
3
92
0
Order By: Relevance
“…Furthermore, two MMP family members, MMP-1 and MMP-2, have been recently found to be important functional mediators in the generation of pulmonary metastases from breast carcinomas (36). Likewise, RNA interference inhibition of MMP-1 prevents melanoma metastasis by reducing tumor collagenase activity and angiogenesis (37). However, the observations reported herein for MMP-8, as well as recent findings for other MMP family members (38)(39)(40)(41)(42), clearly indicate that the cancer protective roles of MMPs may be much more relevant than anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, two MMP family members, MMP-1 and MMP-2, have been recently found to be important functional mediators in the generation of pulmonary metastases from breast carcinomas (36). Likewise, RNA interference inhibition of MMP-1 prevents melanoma metastasis by reducing tumor collagenase activity and angiogenesis (37). However, the observations reported herein for MMP-8, as well as recent findings for other MMP family members (38)(39)(40)(41)(42), clearly indicate that the cancer protective roles of MMPs may be much more relevant than anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, a tumor therapy targeting MMP-2 would be particularly efficacious in the treatment of pancreatic cancer. As a very potent tool, RNAi technology can generate a cellular knockdown of a desired gene utilizing a plasmid-based system that stably expresses siRNA molecules to target specific mRNAs for degradation [9,10] . In this study, we developed a siRNA sequence, when stably integrated into cellular DNA, which can selectively target MMP-2 expression.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, targeted inhibition of heparanase expression by antisense complementary DNA transfection showed a significant reduction in the invasive and metastatic properties of tumor cells in an animal model (Uno et al, 2001). Short hairpin RNAs that mediated the attenuation of MMP expression also prevented the progression of human tumor cells in vivo (Blackburn et al, 2007). Although there is a risk that the metastatic potential of tumor cells may be increased by heparanase expression, we found that the intrathoracic administration of 10 7 PFU of Ad-S/hep alone had no apparent effects on the growth of pleural mesothelioma, indicating that this particular dose of the virus appears to be safe (Figure 6a).…”
Section: Discussionmentioning
confidence: 85%